Effect of mulching and nutrient sources on the production of salad cucumber inside and outside naturally ventilated green house - DAYANA SCARIA MANOJ K. UNNI SONIYA BABY; Er. E. K Mathew (Guide) (Tavanur 2008 Kelappaji College of Agricultural Engineering and Technology)
a study was conducted to compare the growth and yield of salad cucumber inside and outside a naturally ventilated greenhouse. The experiment was done nearer to PFDC building
Effect of mulching and nutrient sources on the production of salad cucumber inside and outside naturally ventilated green house